Oxidative metabolism of photosynthetic species and the exposure to some freshwater and marine biotoxins - Puntarulo, Susana Ángela (2021)
Environmental climate conditions could lead to an increasing global occurrence of microorganism blooms that synthesize toxins in the aquatic environments. These blooms could result in significantly toxic events. Responses of photosynthetic organisms to adverse environmental conditions implicate reactive oxygen species generation; but, due to the presence of a varied cellular antioxidant defense system and complex signaling networks, this oxidative stress could act as an important factor in the environmental adaptive processes. The objective of this review was to assess how some biotoxins are implicated in the generation of oxidative and nitrosative metabolic changes, not only in biotoxin-producing organisms but also in non-producing organisms. Therefore, toxins may modify the oxidative cellular balance of several other species. Hence, the effect of toxins on the oxidative and nitrosative conditions will be evaluated in freshwater and marine algae and vascular plants. The changing climate conditions could act as agents capable of modifying the community composition leading to alterations in the global health of the habitat, risking the survival of many species with ecological relevance.